EFFORTS TO DEVELOP CHILDREN'S LANGUAGE SKILLS THROUGH ROLE PLAYING METHODS IN EARLY CHILDHOOD - Rahma (Adisam Publisher, 2025)
This research aims to explore the effectiveness of role playing methods in developing language skills in early childhood. Starting from the understanding that early childhood is a critical period for language development, this research examines various literature that discusses the application and results of role playing as an educational method. The methodology used includes systematic analysis of data that has been published in educational, psychology and linguistics journals. The research results show that role playing not only improves children's vocabulary, but also syntactic and pragmatic abilities. Children who engage in role-playing activities show significant improvements in the ability to understand and use language effectively and contextually. In addition, this method also supports the development of broader social and cognitive skills, which simultaneously strengthens language acquisition. This research concludes that role playing is a very useful tool in early childhood education, given the broad benefits it offers in the development of language and social competence. The implication for the early childhood education curriculum is that it is recommended to pay more attention to and integrate this method widely in the daily learning process.